Payment of Replacement Money in the Execution of Corporate Assets Based on Bankruptcy Law - Nugraha, Lingga; Israhadi, Evita Isretno (Rechtsnormen: Journal of Law, 2024)
Background: This study examines the legal framework governing the payment of compensation in the execution of corporate assets declared bankrupt under Indonesian bankruptcy law. The research highlights issues such as payment prioritization, creditor protection, and dispute resolution in cases involving bankrupt corporate assets. Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations serves as the primary legal reference. Objectives: The primary objective is to analyze the application of existing legal provisions related to compensation payments in bankruptcy cases. It also seeks to identify challenges in executing bankrupt assets and propose solutions to improve legal certainty and fairness for creditors. Methods: This research employs a normative juridical approach, utilizing legal statutes, court decisions, and scholarly literature to analyze bankruptcy law. A qualitative method is applied to explore the interpretation and application of legal norms. Research Findings: The findings reveal that challenges such as ambiguity in payment prioritization, inconsistent creditor protection, and lengthy dispute resolution processes hinder the effective execution of bankrupt assets. These issues impact the equitable distribution of corporate assets among creditors. Conclusion: A clearer legal framework is essential to protect creditors' rights and ensure the execution process aligns with justice principles. Improved clarity in legal provisions can mitigate existing challenges.